Involvement of Flagella-Driven Motility and Pili in Pseudomonas aeruginosa Colonization at the Air-Liquid Interface - Yamamoto, Kyosuke (Japanese Society of Microbial Ecology/The Japanese Society of Soil Microbiology, 2012)
Many aerobic microorganisms can colonize at the air-liquid interface and form a multicellular structure, known as a pellicle. In this study, the involvement of motility and attachment traits in the Pseudomonas aeruginosa pellicle formation process was investigated. Flagella- and flagellar-motor-deficient mutants exhibited delayed pellicle formation and unusual pellicle morphology, indicating the large contribution of flagella-driven motility to structural development of the pellicle. A pili-deficient mutant showed normal pellicle formation properties, while the disruption of the pilus gene in the flagella-deficient mutant restored normal pellicle morphology. These results indicate that flagella and pili play key roles in P. aeruginosa pellicle development.